The association between fatty acid intake and breast cancer based on the NHANES and Mendelian randomization study. (August 2021) - Guo, Feng; Wang, Min; Guo, Xuecan; Pu, Liyuan; Sun, Mengzi; Li, Shuo; Feng, Tianyu; Tong, Li; Zhao, Saisai; Gao, Wenhui; Lin, Xinli; Yao, Yan; et al.
Highlights: The association between fatty acids intake and BC remains controversial. Higher intake of MUFAs was associated with lower risk of BC in premenopausal women. The protective effect of MUFAs on BC was supported by two-sample MR study. Abstract: Background: Observational studies have examined the association between fatty acid intake and breast cancer (BC), and the association might vary depending on menopausal status, but the results remain controversial. The objective of this study was to investigate the associations between fatty acid intake and BC. Methods: The National Health and Nutrition Examination Survey (NHANES) 1999–2016 was used in the study, and stratified analysis by menopausal status was performed. Logistic regression models were used to evaluate the associations between BC and intake of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs), adjusting for covariates. Three two-sample Mendelian randomization (MR) methods—inverse variance weighted (IVW), weighted median, and Mendelian randomization–Egger (MR-Egger) regression—were applied to further verify the associations between intake of fatty acids and BC. Results: Higher intake of MUFAs was associated with lower risk of BC in premenopausal women: ORs (95 %CI): 0.325 (0.110, 0.964). IVW showed that increased intake of MUFAs was associated with a reduced risk of BC: 0.997 (0.995, 1.000), p = 0.024. No associations between BC and SFAs, MUFAs or PUFAs were found in postmenopausal women or in the overall population. Conclusions: Increasing intake of MUFAs might reduce the risk of BC in premenopausal women. The protective effect of MUFAs on BC was also supported by MR study.